Improving the system of personnel incentives in the oil and gas industry - Kabakova, G.E.; Kazbekova, L.A.; Nakipova, M.B. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: Due to objective reasons, the existing incentive system in the oil and gas industry turned out to be irrelevant and does not correspond to modern Kazakhstan market conditions. The problem is that currently, in the conditions of digitalization and innovative development, changes are taking place in our country, in which we must accept and adapt our development policy to these realities. The purpose of this article is to study new methods for improving existing incentive systems for personnel at oil and gas producing enterprises. Methods: Current personnel problems and documents regulating the activities of the company's employees were reviewed and analyzed in the oil and gas companies of the region, and practical recommendations and methods were given to improve the incentive system and regulations on remuneration of employees in the activities of oil and gas companies. Findings: The importance of applying the calculation of annual, quarterly and monthly bonus payments, the conditions for the payment of bonus payments, the criterion of the employee's efficiency coefficient, additional conditions for the payment of bonus payments to each employee, as well as the frequency of payment of bonus payments was noted. Conclusions: Companies should ensure transparency and openness in personnel management, constantly improve incentive and management methods, provide favorable working conditions, use part of the company's profits for professional development, retraining, obtaining new skills, realizing personal and professional potential by employees.
Мұнай-газ саласындағы персоналды ынталандыру жүйесін жетiлдiру
Совершенствование системы стимулирования персонала в нефтегазовой отрасли
Keywords: incentive system; transformation; personnel policy; personnel potential; digitalization; personnel; competencies; oil and gas industry